2009
DOI: 10.1051/0004-6361:200810967
|View full text |Cite
|
Sign up to set email alerts
|

A sensitivity study of the neutral-neutral reactions C + C$_{\sf 3}$ and C + C$_{\sf 5}$ in cold dense interstellar clouds

Abstract: Aims. Chemical networks used for models of interstellar clouds contain many reactions, some of them with poorly determined rate coefficients and/or products. In this work, we report a method for improving the predictions of molecular abundances using sensitivity methods and ab initio calculations. Methods. Based on the chemical network osu.2003, we used two different sensitivity methods to determine the most important reactions as a function of time for models of dense cold clouds. Of these reactions, we conce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 28 publications
(43 reference statements)
0
62
0
Order By: Relevance
“…We prefer this approach, where C 4 is derived from energy calculations for this specific system, rather than using the recently proposed general scheme for ion-polar molecule reactions (Wakelam et al 2010). With this approach, we take the whole interaction between the two approaching units fully into account, rather than approximating it as a sum of multipole interactions (Wakelam et al 2012). The microcanonical rate constant for each elementary unimolecular step is calculated using the following formula: where N(E) denotes the sum of states in the transition state at energy E, ρ(E) is the reactant density of states at energy E, and h is Planck's constant.…”
Section: Kinetics Calculationsmentioning
confidence: 99%
“…We prefer this approach, where C 4 is derived from energy calculations for this specific system, rather than using the recently proposed general scheme for ion-polar molecule reactions (Wakelam et al 2010). With this approach, we take the whole interaction between the two approaching units fully into account, rather than approximating it as a sum of multipole interactions (Wakelam et al 2012). The microcanonical rate constant for each elementary unimolecular step is calculated using the following formula: where N(E) denotes the sum of states in the transition state at energy E, ρ(E) is the reactant density of states at energy E, and h is Planck's constant.…”
Section: Kinetics Calculationsmentioning
confidence: 99%
“…As in any nucleation based work, we also assume that grain formation and growth take place by the addition of single carbon atoms, and that grain erosion as well takes place by removing one atom at a time from a cluster. Reactions that cause the splitting of a cluster in two fragments are not considered, even though they might be important, especially at low temperatures (see, e.g., Wakelam et al 2009). Another important issue is whether the chemical and nucleation approaches are fully consistent with each other.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, our rate coefficient for this channel is larger than that of Reaction (1) Reducing the uncertainty of the rate coefficient for Reaction (1) has been identified by Wakelam et al (2009Wakelam et al ( , 2010 as being critically important in order to more reliably predict the abundances for a large number of species observed in dense molecular clouds. Similarly, Vasyunin et al (2008) has shown that the uncertainty in this rate coefficient hinders our ability to reliably predict chemical abundances in protoplanetary disks.…”
Section: Introductionmentioning
confidence: 89%